Green Synthesis Nanopartikel Karbon Aktif dari Limbah Tempurung Kelapa - Rena Aprilianti; Dera Selviani; Diani Lestari; Herman Aldila (Jurusan Fisika, Universitas Bangka Belitung, 2023)
Activated carbon from coconut shell waste is a porous solid that has a large surface area with high absorption capacity, making it an alternative for reducing levels of heavy metal ions in the air. Active carbon is made by carbonization and chemical activation, then SEM testing is carried out to see the morphology of the activated carbon and analyzed using ImageJ software. This research aims to determine the effect of chemical activation and no activation on the number of pores formed in activated carbon. From the results of research that has been carried out, there are more pores formed after carbon is activated compared to carbon without activation. This is because the carbon surface without activation is still covered by impurities. In addition, unactivated carbon and activated carbon from coconut shells have pore sizes that fall into the mesoporous category.